High Frequency Plant Regeneration System from Transverse Thin Cell Layer Section of In vitro Derived ‘Nadia’ Ginger Microrhizome - Dikash Singh THINGBAIJAM; Devi Sunitibala HUIDROM (Notulae Scientia Biologicae, 2014)
An efficient and reproducible procedure is outlined for rapid in vitro multiplication of Zingiber officinale var. ‘Nadia’ through high frequency shoot proliferation from transverse thin cell layer (tTCL) sections of in vitro derived microrhizome. In vitro derived microrhizome of size 500 μm in thickness was used as initial explants for induction of somatic embryos. Among the different phytohormones tested, tTCL explants shows maximum calli proliferation in medium containing 2 mg/L 2,4-Dichlorophenoxyacetic acid (88.30±0.11%). Reduced concentration of 2,4 Dichlorophenoxyacetic acid was supplemented with different cytokinins for regeneration of callus. Among the different medium tested, optimum redifferentiation of somatic embryos were observed in medium containing 0.2 mg/L 2,4 Dichlorophenoxyacetic acid and 6.0 mg/L BAP (141.08±0.25). Clump of regenerated plantlets were further subculture and transfer into microrhizome inducing medium containing high sucrose concentration (8%). Plantlets with well developed microrhizome were successfully acclimatized and eventually transferred to the field. The application of studying embryo section for regeneration of plants might be useful alternative to ginger improvement programme. Histological analysis showed formation of somatic embryos and regenerated adventitious shoot.